Komentar dan arah masa depan riset meta-prasangka dan pendekatan human nature - Putra, Idhamsyah Eka (Jurnal Psikologi Sosial, 2025)
This paper discusses the concept of meta-prejudice and the Human Nature approach, including the research conducted and the findings obtained. Starting from the idea of meta-beliefs, Putra developed the concept of meta-prejudice to examine prejudice and intergroup hatred. Unlike Putra (2014), Cahyaningtyas (2015) applied this concept to the realm of male-female relations, particularly in relation to the feminist movement. Furthermore, based on the belief of some lay people that humans are inherently good, Putra (Putra et al., 2018; 2022) developed the Human Nature approach, which is expected to reduce prejudice and intergroup hatred. Most empirical findings so far support this hypothesis. Adopting this concept, Syarif (2025) then examined it in the context of postnatal trauma in fathers. This paper specifically reviews the studies conducted by Cahyaningtyas and Syarif in more detail. In addition, this article also discusses the advantages and limitations of both the meta-prejudice concept and the Human Nature approach, and offers possible directions for further research that can be developed in the future.